Output growth and prices of establishments in the Swedish hotel industry - Martin Falk; Eva Hagsten (European Regional Science Association (ERSA), 2014)
The empirical analysis of firm growth is a classical field in industrial economics. Insights into the determinants of firm growth are particularly interesting for mature markets. A typical example of a mature market is the lodging industry in high-income countries, characterised by a high degree of competition and concentration and declining entry rates (Kalnins, 2006). This paper contributes to the literature by providing first empirical evidence on the determinants of output growth and output prices of establishments in the Swedish hospitality industry. Special focus is placed on the relationship between the quality of accommodation establishments - measured as revenues per overnight stays - and performance in subsequent years. Growth of establishments is measured as the average annual change in overnight stays between the period 2005?2010. Other determinants of establishment growth include establishment size, establishment age and type of hotel (e.g., city hotel, hostels, cottages). The empirical model accounts for potential endogeneity of output prices through the estimation of the 2 stage least square method (2SLS) and two-stage least absolute deviation model (2SLAD) with the number of competitors in given municipality as instrument for prices. In order to allow for heterogeneity of the effects between low and high growth establishments, we use the quantile instrumental variable method which makes it possible to examine the whole distribution of establishment growth and also address the potential endogeneity issue of output prices. In particular, we employ the control function approach introduced by Lee (2007). As instrumental variables for accommodation prices, we use the number of competitors in a given municipality. This paper also contributes to the determinants of prices on the lodging industry. Recent studies show that age, size, location, geographical concentration and share of foreign travellers play a significant role in hotel prices (Becerra, Santaló & Silva, 2013). Unlike most previous studies, we employ the total population of establishments in the lodging industry rather than a selected sample of hotels listed in online booking systems. The availability of unique establishment data for the total population of the lodging industry for Sweden makes it possible to analyse jointly the determinants of growth of establishments and output prices. Data consists of about 2,440 establishments for the period 2005?2010. 2SLS estimates show that high price establishments show a significantly higher output growth rate between 2005 2010. Growth of establishments is significantly higher for smaller and older establishments and city hotels. Furthermore, quantile instrumental variable estimates show that the positive impact of prices on growth only holds true for low growth establishments. Finally, accommodation prices significantly decrease with the number of local competitors with a non-linear form and increase with size and age. City hotels and accommodation in the capital city achieve higher prices.
Keywords: D22; L11; 330; firm growth; establishments; lodging industry; output prices; competition; Sweden